Methodology Features of Creating Distance Learning System “WebAlmir”. - Kruglyk В.С. (Journal of Information Technologies in Education (ITE), 2007)
The article describes the structure of modern pedagogical software, new approaches of working with pedagogical materials, architecture model of pedagogical software tools.